Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Disponible en ligne à https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/racializing-heterosexuality-nonnormativity-and-east-asian-characters-in-james-bond-films/52C50BE7F19552D50389CDED9913BCE3
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »– Quatrième de couverture.
Section: 144 pages ; 23 cm
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires

Territoires en mouvement : femmes et danses de résistance en Arménie - Institut de recherches et d'études féministes
Et si danser devenait un acte de résistance, un territoire à soi quand tout disparaît ? Dans cet épisode, nous partons en Arménie avec Sona Pogossian, où la danse devient un pilier identitaire face à l’enclavement, à la perte de terres, et aux blessures de l’histoire. La danse, architecture vivante et mouvante, est un territoire immatériel que l’on porte en soi. Les femmes y incarnent un double pilier : celui de la mère et celui de la nation. Dans une société où la femme est le noyau de l’identité nationale, comme dans bien d’autres luttes pour l’autodétermination, la figure maternelle devient le symbole d’un « NOUS » collectif, profond et résistant. Biographie : Artiste de la scène, Sona a suivi de multiples formations en anthropologie et pratiques des arts scéniques, dont au sein du conservatoire de Lyon, de l’université d’État de Moscou d’Art et de Culture, de l’université Paris 8, entre autres. Son parcours pluriel l’amène aujourd’hui à réaliser un doctorat (thèse-création) à l’UQAM en études et pratiques des arts, où elle tente de mettre en lumière les corporalités des femmes en phénomène de guerre. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Juliette Chevet et Rajae Anys. Écrit et monté par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; Arménie; arts; asie; danse; discipline; doits des femmes; foire féministe; guerre; maternité; militance; musique; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques